The preliminary assessment of adaptation potential in existing office buildings - Wilkinson, Sara (International Journal of Strategic Property Management, 2014)
It is said that the battle for sustainability will be won or lost in the world’s cities and a major tactic in this challenge will be the sustainable adaptation of existing buildings. Evidence based decision-making tools are required for the management of built assets. This research examined every building adaptation event between 1998 and 2008 with the relative importance of property attributes derived using a principal component analysis (PCA), from which a weighted index of optimal decision- making attributes in a predictive model was proposed; the Preliminary Assessment Adaptation Model (PAAM). The model is discussed and applied in an illustrative case study. Given further development and testing the PAAM might be useable by non-experts and property managers to appraise the suitability of a building for potential adaptation. First Publish Online: 21 Mar 2014